Survivorship: Cognitive Function, Version 1.2014: Clinical Practice Guidelines in Oncology - Denlinger, Crystal S. (J Natl Compr Canc Netw, 2014)
Cognitive impairment is a common complaint among cancer survivors and may be a consequence of the tumors themselves or direct effects of cancer-related treatment (eg, chemotherapy, endocrine therapy, radiation). For some survivors, symptoms persist over the long term and, when more severe, can impact quality of life and function. This section of the NCCN Guidelines for Survivorship provides assessment, evaluation, and management recommendations for cognitive dysfunction in survivors. Nonpharmacologic interventions (eg, instruction in coping strategies; management of distress, pain, sleep disturbances, and fatigue; occupational therapy) are recommended, with pharmacologic interventions as a last line of therapy in survivors for whom other interventions have been insufficient.